ЖАНУБИЙ ОРОЛҚУМ ҲУДУДИНИНГ КАМ ЎРГАНИЛГАН ТЎҒРИҚАНОТСИМОН (INSECTA:ORTHOPTEROIDEA) ҲАШАРОТЛАРИ - Базарбаева, Д.О.; Гулимбетов, Б. (SCIENCE and SOCIETY, 2020)
As a result of research different species of the fauna as right-winged insects in different regions of the southern Aral sea, 9 species and subspecies belonging to 7 families, 9 general of the main family of right-winged insects were identified. The identified right-winged insects, 2 species of cockroach, 4 species of mantis, one specy oftermites, 1 specy of tube formeds eitnor skin-wingeds or 38 species of straight-winged insects are distributed in the study area.